The utility of passive seismic attenuation tomography for monitoring changes in a block caving mine - Jaimes, A.; Birch, D.J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Travel-time tomography is a powerful non-invasive imaging technique that uses the first arrival travel times of P-waves (tp) and S-waves (ts) to infer the velocity of the medium through which seismic waves travel. This methodology has been successfully applied at block caving mines to map spatial and temporal variations in seismic velocities, which are then correlated to changes in the stress state of the rock mass. Much of this success can be attributed to the fact that, in general, seismic travel times, as well as ray paths, are significantly perturbed by the presence of the block cave. Despite their usefulness, velocity tomograms may not properly quantify areas of strong stress fracturing since variations in lithological properties can have a similar effect on the propagation time of seismic waves. Seismic quality factor (Q-1) maps reflect the attenuation of seismic energy, which is highly sensitive to the extent of fracturing and crack accumulation. At block cave mines one is interested in tracking high stress areas. It is therefore beneficial to compute both 3D velocity and Q-1 maps. In this work, we showcase a passive seismic attenuation tomography workflow to image both the velocity and attenuation structure through which seismic waves propagate. We first validate our framework with synthetic tests that use realistic source-to-receiver configurations, as well as physically meaningful velocity and attenuation models computed empirically from numerical stress models. We then use this methodology to obtain velocity and attenuation tomograms from passive seismic data recorded at an Australian block caving mine. These seismic data span a 12-month period and contain records from geophones and distributed acoustic sensing. The velocity and attenuation maps that were obtained are in agreement with previously estimated yielded zones. The attenuation maps, in particular, clearly delineate the progression of the yielded zone. The methodology that we present, and the associated results, highlight the potential of attenuation tomography to image high stress areas around block caving mines, which is of importance for geotechnical analyses.